A cocoon of freshly accelerated cosmic rays detected by Fermi in the Cygnus superbubble - Ackermann, M; Ajello, M; Allafort, A; Baldini, L; Ballet, J; Barbiellini, G; Bastieri, D; Belfiore, A; Bellazzini, R; Berenji, B; Blandford, R D; Bloom, E D; et al. (Science (American Association for the Advancement of Science), 2011)
The origin of Galactic cosmic rays is a century-long puzzle. Indirect evidence points to their acceleration by supernova shockwaves, but we know little of their escape from the shock and their evolution through the turbulent medium surrounding massive stars. Gamma rays can probe their spreading through the ambient gas and radiation fields. The Fermi Large Area Telescope (LAT) has observed the star-forming region of Cygnus X. The 1- to 100-gigaelectronvolt images reveal a 50-parsec-wide cocoon of freshly accelerated cosmic rays that flood the cavities carved by the stellar winds and ionization fronts from young stellar clusters. It provides an example to study the youth of cosmic rays in a superbubble environment before they merge into the older Galactic population.